Frailty Assessment of Transcatheter Aortic Valve Replacement Patients: Contemporary Practice and Future Directions. Issue 4 (4th July 2021) - Chuang, Ming-yu (Anthony); Akodad, Mariama; Chatfield, Andrew; Landes, Uri; Ihdayhid, Abdul; Lal, Sudish; Wood, David A.; Webb, John G; Sathananthan, Janarthanan
ABSTRACT: Frailty is a multi-system clinical syndrome characterized by reduced physiological reserve and increased vulnerability to stressors. There is now established evidence recognizing its incremental value as a predictor of suboptimal outcomes in patients undergoing transcatheter aortic valve replacement (TAVR) beyond conventional surgical risk scores and objective frailty assessment is integrated in major guidelines. Several frailty assessment tools have been developed and validated for use in patients undergoing TAVR with varying complexity, clinical pragmatism and outcomes assessed. In contemporary TAVR practice, frailty assessment guides patient selection, informs care requirements, and identifies those who may require supplemental treatment. Further opportunities to improve patient care in this area include identification of interventions that can mitigate the deleterious impact of frailty, evaluation of the role of frailty assessment in low surgical risk patients, and development of frailty management models that can be delivered virtually. In this review, we aim to provide an overview of the concept of frailty, the available assessment tools, peri-procedural considerations in frail patients undergoing TAVR and future directions.